Upaya Penanggulangan Tindak Pidana Penggelapan Pada Koperasi Kredit (Credit Union) - Mazmur Septian Rumapea; dewi ervina suryani; sonya airini batubara (jurnal.unprimdn.ac.id, 2019)
Credit unions are one of the non-bank financial institutions that have an important role in the Indonesian economy. Because it is related to finance, it is very possible that parties directly related to this matter commit embezzlement. The criminal acts committed will benefit the management of the credit cooperative (credit union). To find out the criminal arrangement of embezzlement in credit unions. This study aims to 1) identify and analyze the efforts to overcome the crime of embezzlement in credit unions. 2) To find out and analyze the efforts to overcome the crime of embezzlement in credit unions. The method used in this research is descriptive analytical using a normative juridical approach supported by an empirical juridical approach. Data that the data used are (1) primary data in the form of interviews with Credit Unions, (2) secondary data through literature studies on various laws and regulations as well as books/journals to obtain expert opinion. The results of this study are expected to published through (1) scientific articles in Accredited National Journals and (2) materials taught in the subject of Criminal Law at the Faculty of Law, University of Prima Indonesia. From the results of this study indicate that efforts to overcome criminal acts of embezzlement can be carried out by means of preventive (prevention) and repressive (enforcement) efforts. Through this publication, it is hoped that credit unions (credit unions) can carry out a strict supervisory function so as to minimize criminal acts of embezzlement in credit unions.